The Facebook-in-action: Challenging, harnessing and enhancing students class assignments and projects - Mohd Saifudin, Adam; Yaacob, Aizan; Saad, Rohaizah (2015)
Issues of universities students harnessing and capitalizing the usage of Facebook for their own learning capabilities and effective thinking is always the focus of education scholars, in assessing the quality class assignments and projects produced by them.Therefore, Facebook is now becoming unbearable influence since the internet activation in the past few years, almost totally interconnected the information sharing and needs among those students.In this action research, the researcher explores the influence and the active usage of Facebook whether that this social media networking are confirmed challenging, enhancing and harnessing the learning capabilities and effective thinking among the university students.Thus they could produce quality class assignments and projects under the supervision of their lecturer concerned.